2015
DOI: 10.1089/dia.2014.0278
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variability Is Associated with Frequency of Blood Glucose Testing and Bolus: Post Hoc Analysis Results from the ProAct Study

Abstract: Introduction: The ProAct study has shown that a pump switch to the Accu-Chek Ò Combo system (Roche Diagnostics Deutschland GmbH, Mannheim, Germany) in type 1 diabetes patients results in stable glycemic control with significant improvements in glycated hemoglobin (HbA1c) in patients with unsatisfactory baseline HbA1c and shorter pump usage time. Patients and Methods: In this post hoc analysis of the ProAct database, we investigated the glycemic control and glycemic variability at baseline by determination of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
1
9
1
1
Order By: Relevance
“…Some studies suggest that patients with DM1 undergoing close monitoring of diabetes through regular HbA1c measurements, blood glucose self-monitoring and regular medical appointments had lower levels of HbA1c. 13 27 28 We found in bivariate analysis, but not in multiple variable analyses, that those self-monitoring blood glucose on a regular basis had lower HbA1c levels. The failure of our multiple variable analyses to show this association may derive from the method that we used to obtain data on blood glucose self-monitoring, which was self-reported, not relying on diaries or other more accurate sources to quantify the daily frequency of self-monitoring in a typical day.…”
Section: Discussioncontrasting
confidence: 62%
“…Some studies suggest that patients with DM1 undergoing close monitoring of diabetes through regular HbA1c measurements, blood glucose self-monitoring and regular medical appointments had lower levels of HbA1c. 13 27 28 We found in bivariate analysis, but not in multiple variable analyses, that those self-monitoring blood glucose on a regular basis had lower HbA1c levels. The failure of our multiple variable analyses to show this association may derive from the method that we used to obtain data on blood glucose self-monitoring, which was self-reported, not relying on diaries or other more accurate sources to quantify the daily frequency of self-monitoring in a typical day.…”
Section: Discussioncontrasting
confidence: 62%
“…A previous study has demonstrated that improvements in glycemic control and glycemic variability were associated with an increased frequency of blood glucose testing and administration of bolus insulin. 30 Other studies have demonstrated that fluctuations in blood glucose levels may contribute more to outcomes than constant high blood glucose concentrations. [31][32][33][34][35] As measurements of HbA 1c do not reflect glycemic variability and target HbA 1c values may be achieved while still experiencing marked daily glycemic fluctuations, people with T1D may regard reducing glucose variability and improving TIR to be as important as achieving their target HbA 1c value.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies investigated associations between behavioral patterns and glycemic control. Pfützner et al 9 reported that pump users performing more frequent fingerstick glucose measurements have better glycemic control and lower glucose variability. This is consistent with our findings that during sensor-augmented pump therapy, the number of fingerstick measurements is associated with lower glucose variability, whereas displaying no such trend during closed-loop period.…”
Section: Discussionmentioning
confidence: 99%